Peer Group Discussion Dalam Penerapan Senam Diabetes Di Posyandu Lansia Desa Pelem Kecamatan Pare Kabupaten Kediri - Nove Lestari; Laviana Nita L; Dewi Taurisyiah Rahayu; Dina Zakiyyatul Fuadah (Universitas Muhammadiyah Klaten, 2023)
DM exercise is an exercise performed by Diabetes Mellittus (DM) sufferers or non-sufferers to prevent injuries and help improve blood circulation. It is recommended for DM sufferers to do light, fast movements for at least 150 minutes every week to burn calories in the body and increase insulin sensitivity. Nurses as part of the health team, apart from playing a role in providing health education, can also play a role in guiding DM sufferers to do foot exercises until the sufferer can do foot exercises independently. The inability of diabetes mellitus patients to carry out self-care can affect the quality of life in terms of physical health, psychological well-being, social relationships and environmental relationships. Self care carried out for diabetes mellitus sufferers is more focused on preventing complications and controlling blood sugar. One of the self-care measures for DM patients is exercise or physical exercise. Exercising regularly can reduce and maintain normal blood sugar levels. One of the foot exercises for diabetes mellitus patients is diabetic foot exercises. This community service method is observational. This program includes all matters of a technical, managerial and scheduling nature (time schedule). The management module includes mentoring, handling and continuous counseling techniques. Preparation of training facilities and infrastructure. This preparation includes the provision of facilities and infrastructure for training places and counseling. Field coordination. From this activity it can be concluded that all participants (100%) understand diabetes mellitus exercise, the purpose of doing foot exercises, know the benefits of DM exercise, know the indications and contraindications for foot exercise and are enthusiastic, attentive and active during DM exercise training activities.